2018
DOI: 10.1021/acs.jpcb.8b08193
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Crystallization of Isotactic Poly(methyl methacrylate) from Different States on Highly Oriented Polyethylene Thin Film

Abstract: Through fixing the orientation of oriented polyethylene (PE) thin film during melt-recrystallization with the help of a vacuum evaporated thin carbon layer, the isothermal melt- and cold-crystallization of isotactic poly(methyl methacrylate) (iPMMA) on oriented PE substrate was studied. The results show that same parallel chain epitaxy of iPMMA on the oriented PE substrate takes place in both cold- and melt-crystallization processes based on a two-dimensional lattice matching. However, the crystallization kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…Consequently, the orientation of the crystal could not propagate by epitaxial growth. For lamellar polymer crystals, only the ( hk 0) planes can assure oriented crystal growth. Nonetheless, in our study, we observed large stacks of flat-on crystals uniquely oriented in the plane. Accordingly, the mechanism of this crystallization process leading to stacking must differ from epitaxial crystallization.…”
Section: Resultsmentioning
confidence: 48%
“…Consequently, the orientation of the crystal could not propagate by epitaxial growth. For lamellar polymer crystals, only the ( hk 0) planes can assure oriented crystal growth. Nonetheless, in our study, we observed large stacks of flat-on crystals uniquely oriented in the plane. Accordingly, the mechanism of this crystallization process leading to stacking must differ from epitaxial crystallization.…”
Section: Resultsmentioning
confidence: 48%
“…As already presented in the introduction part as Figure a, the melt‐drawn iPBu thin films exhibit a fibrillar structure of its form I crystals. However, the morphology of the melt‐drawn PE thin films is totally different from that of iPBu . Figure shows the phase contrast BF electron micrograph and its corresponding ED pattern of a melt‐drawn PE ultrathin film.…”
Section: Techniques For Preparing Highly Oriented Polymer Thin Filmsmentioning
confidence: 98%
“…The electron diffraction pattern is given in the same chain orientation as the BF image. Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Techniques For Preparing Highly Oriented Polymer Thin Filmsmentioning
confidence: 99%
“…On the other hand, the crystallization of poly[(R)-3-hydroxybutyrate] (PHB) in its miscible blends with PVDF under strain causes an a-axis orientation of PHB along the stretching direction [21]. For the crystalline/crystalline polymer blends, the crystal structure and orientation of later crystallized components can be controlled by epitaxy or transcrystallization at the surface of early formed crystals [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37], which may not reflect the effect of strain and the blending component on the later crystallized component correctly. It should be pointed out that soft epitaxy can hardly take place in crystalline/amorphous polymer blends, since it is not a common phenomenon [38,39].…”
Section: Introductionmentioning
confidence: 99%